Phage Biocontrol of Bacterial Leaf Blight Disease on Welsh Onion Caused by Xanthomonas axonopodis pv. allii - Nguyen Thi Thu Nga; Tran Ngoc Tran; Dominique Holtappels; Nguyen Le Kim Ngan; Nguyen Phuoc Hao; Marta Vallino; Doan Thi Kieu Tien; Nguyen Huan Khanh-Pham; Rob Lavigne; Kaeko Kamei; Jeroen Wagemans; Jeffrey B. Jones (Antibiotics, 2021)
Bacterial leaf blight, which is caused by Xanthomonas axonopodis pv. allii, annually causes significant yield losses to Welsh onion in many producing countries, including Vietnam. In this study, we isolated and characterized lytic phages Φ16, Φ17A and Φ31, specific to X. axonopodis pv. allii and belonging to a new phage species and genus within the Autographiviridae, from four provinces in the Mekong Delta of Vietnam. Moreover, we evaluated their efficacy for the biocontrol of leaf blight in greenhouse and field conditions. When applying the three highly related phages individually or as a three-phage cocktail at 108 PFU/mL in greenhouse conditions, our results show that treatment with Φ31 alone provides higher disease prevention than the two other phages or the phage cocktail. Furthermore, we compared phage concentrations from 105 to 108 and showed optimal disease control at 107 and 108 PFU/mL. Finally, under field conditions, both phage Φ31 alone and the phage cocktail treatments suppressed disease symptoms, which was comparable to the chemical bactericide oxolinic acid (Starner). Phage treatment also significantly improved yield, showing the potential of phage as a biocontrol strategy for managing leaf blight in Welsh onion.